“You Feel The Threat From Asia”. Onshore Experiences of IT Offshoring To India - Blomqvist, Martha; Peterson, Helen; Dhar-Bhattacharjee, Sunrita (Nordic Journal of Working Life Studies, 2015)
This article investigates the experiences of employees and managers in Swedish companies that offshore IT services to India, focusing on how implementation of offshoring is changing the work organization and working conditions for software developers onsite. Our analysis highlights the fact that the working conditions have been significantly redesigned in several different ways because of offshoring, most obviously due to the need for knowledge transfer between the onshore and the offshore working sites. The study illustrates how employees and managers onsite utilized different strategies for knowledge transfer and how these strategies were more or less successful, sometimes due to resistance from employees. The article concludes that, although offshoring contributed to a separation of conception from execution in these companies, there were few signs of routinization of daily work tasks for onsite employees. Instead, it was the routinized and noncore tasks that were offshored while project management tasks were taken over by onsite staff, which meant that they ended up in a superior position vis-à-vis their Indian colleagues as new global hierarchies were created. Power relations at work, both within firms and between firms, are thus brought to light.